Percepatan Pembangunan Berbasis Sektor Kunci di Provinsi Lampung Tahun 2018 (Analisis Input Output) - Ambya Ambya (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2022)
The business sector in Lampung Province is the foundation for improving the regional and regional economy. Associated with increasing the added value of superior products, it is necessary to do a mapping of the leading sectors in Lampung Province using input-output analysis. Thus, the purpose of this study is to find out which business sector is a key sector for accelerating development in Lampung Province in 2018, using the 2010 input-output analysis method by updating data on the basis of 2018 producer prices by classifying 34 Field Sectors. Business. The results of this study are presented by making a typology (interaction) between the backward linkage coefficient, and the forward linkage coefficient of the production sector as a whole, so that the sector becomes the main priority in order to accelerate development in Lampung Province based on indirect linkages. namely the Horticultural Crops Sector; and the Highway Transportation sector; and key sectors based on direct linkages, namely: Horticultural Crops; Processing industry; Electricity; and Highway Transportation.